COMPARING GOOGLE TRANSLATE AND INSTAGRAM ENGLISH TRANSLATIONS OF CAPTIONS - Dwi Ningrum (Universitas Negeri Manado, 2022)
Nowadays, machine translators like Google Translate are widely used by people. However, it does not mean that machine translators can always be relied on and produce good translations. This study aimed to analyze the translation quality of Instagram Machine Translation and Google Translate in terms of accuracy, acceptability, and readability. The objective of this research was to find out which machine translator is better between Instagram Machine Translation and Google Translate in translating Instagram captions. The data from the questionnaire were described in qualitative form. Nababan's translation quality instrument (2012) was adopted to assess the quality of the translation results from Google Translate and Instagram Machine Translation, where the translations were assessed with points one, two, or three according to the quality of the translation. The results of the analysis show that in three aspects, namely accuracy, acceptability, and readability, Google Translate is superior to Instagram Machine Translation.